EAACI Guidelines on allergen immunotherapy: IgE‐mediated food allergy - Pajno, G. B.; Fernandez‐Rivas, M.; Arasi, S.; Roberts, G.; Akdis, C. A.; Alvaro‐Lozano, M.; Beyer, K.; Bindslev‐Jensen, C.; Burks, W.; Ebisawa, M.; Eigenmann, P.; Knol, E.; et al. (Allergy (Copenhagen), 2018)
Food allergy can result in considerable morbidity, impairment of quality of life, and healthcare expenditure. There is therefore interest in novel strategies for its treatment, particularly food allergen immunotherapy (FA‐AIT) through the oral (OIT), sublingual (SLIT), or epicutaneous (EPIT) routes. This Guideline, prepared by the European Academy of Allergy and Clinical Immunology (EAACI) Task Force on Allergen Immunotherapy for IgE‐mediated Food Allergy, aims to provide evidence‐based recommendations for active treatment of IgE‐mediated food allergy with FA‐AIT. Immunotherapy relies on the delivery of gradually increasing doses of specific allergen to increase the threshold of reaction while on therapy (also known as desensitization) and ultimately to achieve post‐discontinuation effectiveness (also known as tolerance or sustained unresponsiveness). Oral FA‐AIT has most frequently been assessed: here, the allergen is either immediately swallowed (OIT) or held under the tongue for a period of time (SLIT). Overall, trials have found substantial benefit for patients undergoing either OIT or SLIT with respect to efficacy during treatment, particularly for cow's milk, hen's egg, and peanut allergies. A benefit post‐discontinuation is also suggested, but not confirmed. Adverse events during FA‐AIT have been frequently reported, but few subjects discontinue FA‐AIT as a result of these. Taking into account the current evidence, FA‐AIT should only be performed in research centers or in clinical centers with an extensive experience in FA‐AIT. Patients and their families should be provided with information about the use of FA‐AIT for IgE‐mediated food allergy to allow them to make an informed decision about the therapy.